Global Regularity Criterion for the Magneto-Micropolar Fluid Equations - Fanhui Meng; Gang Wang (Discrete Dynamics in Nature and Society)
We are concerned with the magneto-micropolar fluid equations in . Using Littlewood-Paley decomposition, we obtain an Osgood type global regularity criterion for the system.